Development of Traditional Islamic Boarding Schools Education System In Modernization Era - Zainuddin, Moh Riza (EDUKASI: Jurnal Pendidikan Islam, 2018)
The presence of Islamic boarding schools as an educational institution of Islam, is now increasingly in demand by many, including the upper middle class society. This proves the institution is able to provide solutions to the educational needs of their children. The challenges faced by this institution according to the observations of experts are increasingly more complex, and urgent. This is due to the progress of science and technology (Science and Technology). In the midst of the progress of science and technology that became the motor of modernization movement, today many people feel doubt about the existence of pesantren education institutions. The doubt is based on the tendency of the pesantren to be self-close to the changes around it and the stoicism in responding to the modernization effort. The development of the world has spawned a modern age advancement. The fundamental changes in the cultural structure of society often strike at various establishments. Consequently there is a necessity to hold contextualization efforts of community cultural buildings with the dynamics of modernization, not least with the pesantren education system. Therefore, the pesantren education system must make constructive efforts to remain relevant and able to survive.